2017
DOI: 10.21873/invivo.11108
|View full text |Cite
|
Sign up to set email alerts
|

Elevated IL-4 and IFN-γ Levels in Muscle Tissue of Patients with Dermatomyositis

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…The pathogenesis of DM is an interplay of environmental triggers and autoimmune reactions in individuals who are genetically susceptible . Studies from 2002 to 2020 revealed the role of cytokines and IFN in DM, including IFNγ and STAT pathways, TNF α, IL-4, IL-6, IL-17, IL-18, and IL-23. In addition, response to treatment and improvement in disease activity have been observed with downregulation of the aforementioned interferons and cytokines .…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of DM is an interplay of environmental triggers and autoimmune reactions in individuals who are genetically susceptible . Studies from 2002 to 2020 revealed the role of cytokines and IFN in DM, including IFNγ and STAT pathways, TNF α, IL-4, IL-6, IL-17, IL-18, and IL-23. In addition, response to treatment and improvement in disease activity have been observed with downregulation of the aforementioned interferons and cytokines .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we detected positive associations between Hsp90 levels and MCP-1 and IL-4. Interestingly, both MCP-1 and IL-4 have been implicated in the pathogenesis of IIM [ 21 , 22 , 33 , 34 , 35 , 66 , 67 , 68 ]. Nonetheless, in most cases, inflammatory cytokines/chemokines are not systemically upregulated in healthy volunteers following similar protocols [ 48 , 69 , 70 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of dermatomyositis is multifactorial with environmental, genetic, and immune factor contribution 1 . T helper-1 (Th1) and T helper-2 (Th2) immune pathways play a fundamental role in dermatomyositis 8 . There is an increase in proinflammatory cytokines including tumor necrosis factor α, interleukin (IL)-1, IL-6, and interferon-α and interferon-γ, all of which shift the immune balance to a Th1 response 1 .…”
Section: Discussionmentioning
confidence: 99%
“…There is an increase in proinflammatory cytokines including tumor necrosis factor α, interleukin (IL)-1, IL-6, and interferon-α and interferon-γ, all of which shift the immune balance to a Th1 response 1 . IL-4 released by lymphocytes infiltrating the skin and muscles in dermatomyositis patients contributes to increase in Th2 response in conjunction with Th1 response 8 …”
Section: Discussionmentioning
confidence: 99%